A ingerência humanitária no contexto da regulamentação jurídica da guerra - Nhanombe, Armindo Armando (2019)
In this dissertation, we discuss the humanitarian interference in the context of the legal regulamentarion of war, in the assistance role. This subject which is so important and nowadays very outspoken, belongs to the humanitarian international público law. The humanitarian interference it is an institute used in war conflicts and or natural disasters. It is aimed at saving human lives, under UN Resolution 45/100. This intervention can be conducted through humanitarian assistance, our main focus here, or by the use of armed power. It is our opinion that, following the literature review that we consucted, that interference it is not only a matter of law but also a duty. This development as a new paradigm, has begun from activists Mario Betatti, Bernard Kouchner and other authors that put pressure on the United Nations to look at the issue of interference as a duty which is above all structures. With the Paris first International Conference in January 1987, on Law and Humanitarian Morality, the need to break the principle of non interference to assist victims of war and natural disasters, by NGO’s.